Phylogeny and systematics of Simaba Aubl. (Simaroubacea) - Devecchi, Marcelo Fernando (2017)
Simaba, as traditionally and currently circumscribed, is the largest genus in the Simaroubaceae and is mostly restricted to tropical South America with a few species extending northward into Central America. The genus encompasses a large morphological heterogeneity, expressed in the vegetative and reproductive morphology, and many of its species are narrow endemics, most of them poorly known. Our phylogenetic analyses based on DNA sequence data from two nuclear ribosomal spacer regions (ITS and ETS) and three plastid regions (rps16 intron, and intergenic spacers psbA-trnH and trnL-trnF), including a comprehensive sampling of species of Simaba and closely related genera, show that Simaba as traditionally circumscribed is not monophyletic, with taxa segregated into two strongly supported but distinct clades. Also, we performed ancestral character reconstructions to identify morphological characters that could serve as synapomorphies for major clades. Based on the results of the phylogenetic analyses performed, a division of Simaba s.l. into two distinct genera is here proposed. The clade composed by species of Simaba sect. Tenuiflorae Engl., which includes the type species of Simaba, is here proposed to be recognized as Simaba sensu stricto, while the species of Simaba formerly included in S. sect. Grandiflorae Engl. and S. sect. Floribundae Engl. form a distinct lineage that will be recognized as members of another genus, Homalolepis Turcz., a taxon currently treated in synonymy of Simaba. As here circumscribed, Simaba s.s. comprises approximately 10 species distributed mostly in the Amazonian region, and Homalolepis comprises 28 species with mostly extra-Amazonian distribution, mainly in the cerrado and Atlantic forest domains. In addition to molecular data support, several morphological characters corroborate the recognition of the two clades as distinct lineages. We provide a synopsis of Simaba s.s., including an emended description of the genus, the description of four new species, complete nomenclature for each accepted species, including new lectotypifications. We also present a taxonomic treatment of Homalolepis, with a key for two sections and species, data on nomenclatural types, including new lectotypifications and one epitype, complete synonymy, full morphological descriptions, including two new species, etymology of species names, common names and uses, illustrations and photos of live specimens, as well as comments on phenology, taxonomy and nomenclature. Distribution maps are provided for each species, along with biogeographical and ecological comments